A COMPARATIVE ANALYSIS OF THE CHARACTERS OF KING ARTHUR AND ALPOMISH IN ENGLISH AND UZBEK FOLKLORE LITERATURE (Scientific journal of the Fergana State University, 2024)
The comparative analysis examines the characters of King Arthur from English folklore and Alpomish from Uzbek folklore, exploring the similarities and differences in their roles, narratives, and cultural contexts. Both figures represent heroic ideals in their respective cultural traditions, embodying leadership, chivalry, and a commitment to justice. The analysis delves into their birth and upbringing, the symbolism of their legendary weapons (Excalibur for Arthur and the sword of Alpomish), their quests and adventures, as well as the themes of love and betrayal present in their stories. By juxtaposing these iconic figures, the study aims to shed light on the distinct cultural values and storytelling traditions encapsulated in English and Uzbek folklore literature, contributing to a deeper understanding of the diverse ways in which heroism is portrayed across different cultures.